'I read, I don't understand': refugees coping with academic reading. (24th November 2014) - Hirano, Eliana
Abstract: This article investigates the experience of seven refugee students with academic reading during their first year of college, with a focus on the challenges they faced completing assigned readings and the strategies they used to cope with these challenges. Although the participants graduated from American high schools, they were not considered 'college-ready', according to their scores in standardized exams. Data were collected over two semesters through interviews with participants and faculty, class observations, and written documents such as assigned readings. Data analysis followed qualitative procedures. Findings show that all seven participants were able to cope with academic reading in first-year college, despite the numerous difficulties they faced. This article has implications for college instructors teaching not only refugee students but also teaching any of the growing number of international students currently attending higher education worldwide.